Theoretical Analysis of the Use of Social Scenario-Based “Diversity Card” Media in Tolerance Learning - Cindy Angga Setyawati (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Learning tolerance in PPKn subjects still focuses on cognitive aspects through conceptual explanations and memorization, so that students' tolerant attitudes have not been fully realized in everyday life. The use of